2023
DOI: 10.3389/fdgth.2023.1139210
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and legal considerations influencing human involvement in the implementation of artificial intelligence in a clinical pathway: A multi-stakeholder perspective

Abstract: IntroductionEthical and legal factors will have an important bearing on when and whether automation is appropriate in healthcare. There is a developing literature on the ethics of artificial intelligence (AI) in health, including specific legal or regulatory questions such as whether there is a right to an explanation of AI decision-making. However, there has been limited consideration of the specific ethical and legal factors that influence when, and in what form, human involvement may be required in the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…Across 44 studies, 689 participants were interviewed and 402 participated in focus groups. 31 studies conducted interviews, 16 , 24 , 25 , 31 , 32 , 34 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 48 , 49 , 50 , 51 , 53 , 55 , 57 , 59 , 60 , 61 , 62 , 63 , 64 nine conducted focus groups, 18 , 26 , 27 , 29 , 30 , 33 , 52 , 56 , 58 , 65 five conducted ethnographic studies with interviews, 17 , 46 , 47 , 54 , 66 and two conducted both interviews and focus groups. 35 , 47 The mean number of participants in interview studies was 20 (IQR 15–24), and in focus groups 40(IQR 15–37).…”
Section: Resultsmentioning
confidence: 99%
“…Across 44 studies, 689 participants were interviewed and 402 participated in focus groups. 31 studies conducted interviews, 16 , 24 , 25 , 31 , 32 , 34 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 48 , 49 , 50 , 51 , 53 , 55 , 57 , 59 , 60 , 61 , 62 , 63 , 64 nine conducted focus groups, 18 , 26 , 27 , 29 , 30 , 33 , 52 , 56 , 58 , 65 five conducted ethnographic studies with interviews, 17 , 46 , 47 , 54 , 66 and two conducted both interviews and focus groups. 35 , 47 The mean number of participants in interview studies was 20 (IQR 15–24), and in focus groups 40(IQR 15–37).…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] Ethical considerations and regulatory frameworks are additional, well recognized challenges for AI deployment in health care, that need to be addressed. [41][42][43][44][45] Here, we applied methods to reduce the propensity for language biases, inaccuracies, and potential for hallucinations; however, they will nevertheless occur at some frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical considerations and regulatory frameworks are additional, well recognized challenges for AI deployment in health care, that need to be addressed. [4145] Here, we applied methods to reduce the propensity for language biases, inaccuracies, and potential for hallucinations; however, they will nevertheless occur at some frequency. When combined with privacy considerations that arise when data are shared in non-restricted environments in order to enable the language models to function, there are clear needs to develop additional approaches to protect patient rights and data security, and maintaining the overall safety and effectiveness of AI applications in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study revealed the evolving impact of AI on patient–provider interactions is an essential aspect of the discussion surrounding AI in healthcare. The concerns about communication challenges with AI reflect a potential source of friction between patients and AI-driven healthcare systems ( Redrup Hill et al, 2023 ). Effective AI–patient communication is vital to ensure patients’ needs are accurately understood and met.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of legal implications, especially concerning liability in cases of AI errors, underscores the need for clarity and legal frameworks that address these challenges ( Silva et al, 2022 ). Additionally, Redrup Hill et al (2023) highlights the need for interdisciplinary collaboration in addressing liability challenges. They argue that legal frameworks should be developed with input from experts in both AI and healthcare, ensuring a nuanced understanding of the potential risks and consequences associated with AI errors.…”
Section: Discussionmentioning
confidence: 99%